2016
DOI: 10.2134/agronj2016.03.0139
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Optimum Nitrogen Rates for Maize

Abstract: Maize (Zea mays L.) grain yield levels and the response to fertilizer nitrogen (N) are expected to change from year to year and from location to location. Because yield level and N response have been documented to be independent and are known to infl uence N demand, optimum N rates at the same location vary each year due to unpredictable changes in the environment. Th e objective of this study was to further analyze maize grain yield levels and optimum fertilizer N rates from published data in maize growing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 69 publications
(85 reference statements)
4
66
0
Order By: Relevance
“…Over much of the maize-producing landscape in the United States, recent work has documented that optimum fertilizer N rates are highly variable and fluctuate from 1 yr to the next, at the same site (Dhital and Raun, 2016). Work by Huang et al (2016) further noted temporal variation in atmospheric N deposition, as an important N source in agro-ecosystems, and that has increased in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over much of the maize-producing landscape in the United States, recent work has documented that optimum fertilizer N rates are highly variable and fluctuate from 1 yr to the next, at the same site (Dhital and Raun, 2016). Work by Huang et al (2016) further noted temporal variation in atmospheric N deposition, as an important N source in agro-ecosystems, and that has increased in China.…”
Section: Discussionmentioning
confidence: 99%
“…Wide-ranging work by Dhital and Raun (2016), employing 213 site-years of maize data showed that optimum N rates fluctuated from year to year at all locations. They further reported the need to adjust fertilizer N rates by year and location in regions where historically, the same rates are being applied year after year.…”
mentioning
confidence: 99%
“…Lucie A. Kablan,* Valérie Chabot, Alexandre Mailloux, Marie-Ève Bouchard, Daniel Fontaine, and Tom Bruulsema rates observed across corn experiments (213 site-years) in the United States suggests the need to adjust N rates by year and location (Dhital and Raun, 2016). Soil texture is another important factor that influences EONR.…”
Section: Variability In Corn Yield Response To Nitrogen Fertilizer Inmentioning
confidence: 99%
“…specific to corn in the United States are the field-to-field variability reported by Bundy and Andraski (1995), Schmitt and Randall (1994), and Lory and Scharf (2003), and year-to-year variability across fields reported by Dhital and Raun (2016). Equally important are reports documenting wide withinfield variability in EONRs Mamo et al, 2003;Scharf et al, 2005;Schmidt et al, 2007;Cao et al, 2012).…”
mentioning
confidence: 99%